Realising a layered digital library: Exploration and analysis of the Live Music Archive through linked data - Page, K; Bechhofer, S; Fazekas, G; Weigl, K; Wilmering, T (Institute of Electrical and Electronics Engineers, 2017)
Building upon a collection with functionality for discovery and analysis has been described by Lynch as a ‘layered’ approach to digital libraries. Meanwhile, as digital corpora have grown in size, their analysis is necessarily supplemented by automated application of computational methods, which can create layers of information as intricate and complex as those within the content itself. This combination of layers – aggregating homogeneous collections, specialised analyses, and new observations – requires a flexible approach to systems implementation which enables pathways through the layers via common points of understanding, while simultaneously accommodating the emergence of previously unforeseen layers. In this paper we follow a Linked Data approach to build a layered digital library based on content from the Internet Archive Live Music Archive. Starting from the recorded audio and basic information in the Archive, we €rst deploy a layer of catalogue metadata which allows an initial – if imperfect – consolidation of performer, song, and venue information. A processing layer extracts audio features from the original recordings, workƒow provenance, and summary feature metadata. A further analysis layer provides tools for the user to combine audio and feature data, discovered and reconciled using interlinked catalogue and feature metadata from layers below Finally, we demonstrate the feasibility of the system through an investigation of ‘key typicality’ across performances. This highlights the need to incorporate robustness to inevitable ‘imperfections’ when undertaking scholarship within the digital library, be that from mislabelling, poor quality audio, or intrinsic limitations of computational methods. We do so not with the assumption that a ‘perfect’ version can be reached; but that a key bene€t of a layered approach is to allow accurate representations of information to be discovered, combined, and investigated for informed interpretation.